Analysis of Allocative and Economic Efficiency of Corn Farming - Jullyo Gideon Rohi; Frengky Lambu Apu (UNIVERSITAS SEMBILANBELAS NOVEMBER KOLAKA, 2025)
Corn is the main commodity in dry land farming for most farmers in NTT Province and acts as a food source to maintain food security and as a source of income (cash income). Kupang Regency is one of the corn centre districts in NTT Province because it prioritises economic development in the agricultural sector in the food crop sub-sector. This study aims to measure the level of allocative efficiency of the use of corn farming production factors. This research was conducted in Kupang Timur District, Kupang Regency, East Nusa Tenggara Province in 2024. The research was conducted using a survey method with simple random sampling. The sample determined as respondents was 92 farmers based on the area of cultivated land. The method used is the calculation of marginal product analysis, used to measure allocative efficiency and economic efficiency, which is measured by the division between technical and allocative efficiency. The results of the research analysis show that the factors that have a significant effect on corn farming production are land area, seeds, urea, KCL, SP36 and Pesticides. Furthermore, from the results of the analysis of allocative and economic efficiency, the efficiency values for the overall farmer category are 0.47 and 0.35, respectively and based on the division of land area, it shows that corn farming in East Kupang District is still inefficient. Corn farming efficiency needs to be improved through the use of production factors that have a significant effect on technical efficiency, such as land area and the addition of technology. Allocative and economic efficiency of corn farming can also be improved by reducing the use of excessive inputs and expensive input prices that which can save high farming costs so that it can affect farmers' income.